Organisational culture as a determinant of business process management in the community offices in Poland - Magdalena Raczyńska; Krzysztof Krukowski (Administrative Sciences, 2019)
The application of business process management (BPM) in public organizations is determined by multiple factors and, according to numerous studies, organizational culture is one of them. Therefore, the aim of the study presented in the article was to identify the organizational culture factors which occur in community offices in Poland. Subsequently, the identified factors were assessed in the context of their significance in the introduction and development of BPM in the examined entities. As a result of the conducted study, it was possible to indicate not only the factors, which have the potential to stimulate the implementation and extension of the concept in the community offices, but also the elements recognized as its barriers. Among the factors that can be considered as the mentioned stimulants, these were: the possibility of exchanging opinions with one's superiors and colleagues, the will to learn and to broaden one's knowledge, good and friendly interpersonal relations, or an orientation towards service quality. And among the elements that can be perceived as barriers, one can identify a lack of positive attitude to change or the formalization arising from the law.
Keywords: 350; organizational culture; business process management; public organization; community office